EFEKTIVITAS PENGGUNAAN MEDIA INTERAKTIF DALAM MENINGKATKAN KEMAMPUAN LISTENING BAHASA INGGRIS - Syarifah Siregar (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
This study aims to examine the effectiveness of using interactive media in enhancing students' listening skills in English. The research employs a library research method, which involves collecting and analyzing literature from journals, books, conference proceedings, and educational policy documents relevant to the topic. Data were collected from literature published in the last five years (2020–2023), focusing on interactive media, listening skills, and educational technology. The analysis reveals that the application of interactive media, such as videos, podcasts, and educational apps, significantly improves student engagement and motivation, while effectively enhancing listening abilities. Digital platforms, including podcasts and mobile apps, provide authentic, flexible learning experiences that are relevant to students' daily lives. Additionally, Android-based applications foster independent learning and enhance students' autonomy in managing their study time and environment. Based on these findings, it is recommended that educators integrate interactive media into the English curriculum to create a more engaging, effective, and technology-aligned learning environment